Evolving an Information Systems Capstone Course to Align with the Fast Changing Singapore Marketplace - BOESCH, Chris (Institutional Knowledge at Singapore Management University, 2014)
Every year, around fifty-five undergraduate teams of four to six students are required to complete a capstone course for the School of Information Systems at Singapore Management University. Each team spends approximately five months working with an industry sponsor using the latest tools and techniques. Students actively learn by implementing the system to solve a real world problem. In addition to delivering value to the local sponsor, our students learn specialized skills currently needed in the marketplace, which might not yet be incorporated into electives and core courses. In this paper, we discuss the tradeoffs of providing students and project sponsors flexibility in designing projects while at the same time ensuring that all students are delivering consistent, assessable milestones. We will also discuss how the tools and techniques available to students are continually changing what the students are able to accomplish in a fixed amount of time.